2019
DOI: 10.1038/s41467-019-10296-9
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-tetrodotoxin conjugates to induce prolonged duration local anesthesia with minimal toxicity

Abstract: There is clinical and scientific interest in developing local anesthetics with prolonged durations of effect from single injections. The need for such is highlighted by the current opioid epidemic. Site 1 sodium channel blockers such as tetrodotoxin (TTX) are extremely potent, and can provide very long nerve blocks but the duration is limited by the associated systemic toxicity. Here we report a system where slow release of TTX conjugated to a biocompatible and biodegradable polymer, poly(triol dicarboxylic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 32 publications
0
72
0
Order By: Relevance
“…Conjugate delivery systems overcome the main drawbacks of non-covalent physical methods, unfavorable leakage and burst release, due to stable linkers between drugs and polymers (Chen et al, 2014). Zhao et al (2019) synthesized a range of rationally designed PEGylated and non-PEGylated polymers to which the ultra-potent local anesthetic TTX was conjugated by hydrolysable ester bonds. Zhao demonstrated that TTX was released in its native form, and the release rate can be regulated by manipulating the polymer composition (the TTX release rate is proportional to the hydrophilicity of polymer backbone).…”
Section: Conjugate Delivery Systemmentioning
confidence: 99%
“…Conjugate delivery systems overcome the main drawbacks of non-covalent physical methods, unfavorable leakage and burst release, due to stable linkers between drugs and polymers (Chen et al, 2014). Zhao et al (2019) synthesized a range of rationally designed PEGylated and non-PEGylated polymers to which the ultra-potent local anesthetic TTX was conjugated by hydrolysable ester bonds. Zhao demonstrated that TTX was released in its native form, and the release rate can be regulated by manipulating the polymer composition (the TTX release rate is proportional to the hydrophilicity of polymer backbone).…”
Section: Conjugate Delivery Systemmentioning
confidence: 99%
“…In humans, 30 μg of TTX administered subcutaneously twice a day for 4 days was reported to be safe and well tolerated (Hagen et al, 2017). In addition, new biodegradable polymers have recently been developed for therapeutic delivery of TTX to achieve prolonged and local sodium channel blockade without detectable systemic toxicity (Zhao et al, 2019). Thus, there may be a path forward to apply this strategy for the treatment of deprivation amblyopia in adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…The release rate can be tuned by adjusting the chemical linker type and the large molecules' chemical composition. For example, when a drug binds to a polymer through an ester bond, the drug is released by hydrolysis of the ester bond, and the hydrolysis rate can be reduced by increasing the hydrophobicity of the polymer chain (Zhao et al, 2019). Covalent bonds are more stable than non-covalent bonds; therefore, less drug is released prematurely, and sudden initial drug release is reduced.…”
Section: Cavity Loadingmentioning
confidence: 99%
“…In addition to the carrier itself, solvent residues in the carrier can also cause biocompatibility issues. Organic solvents are used usually in the manufacturing or processing of formulations, such as dissolving polymers for emulsification to prepare nanoparticles (Zhang et al, 2016), dissolving lipids to prepare liposomes through the film hydration method (Shomorony et al, 2019), and in the reactions to covalently bind drug to the large molecules (Zhang et al, 2020;Zhao et al, 2019). The solvents present in the final product must be below the limits set by the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH) as they are potentially harmful to those consuming these products.…”
Section: Biocompatibility Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation